Measuring the preferences of homeless women for cervical cancer screening interventions: development of a best-worst scaling survey - Wittenberg, Eve (Patient, 2015)
OBJECTIVE: Despite multiple risk factors, women experiencing homelessness are screened for cervical cancer at a lower rate than women in the general US population. We report on the design of a stated preference study to assess homeless women's preferences for cervical cancer screening interventions, to inform efforts to overcome this disparity. METHODS: We conducted focus groups with homeless women (n=8) on cervical cancer screening decisions, and analyzed data using thematic analysis. We applied inclusion criteria to select factors for a stated preference survey: importance to women, relevance to providers, feasibility, and consistency with clinical experience. We conducted pre-tests (n=35) to assess survey procedures (functionality, recruitment, administration) and content (understanding, comprehension, wording/language, length). RESULTS: We chose best-worst scaling (BWS, also known as object scaling) to identify decision-relevant screening intervention factors. We chose an experimental design with 11 “objects” (i.e., factors relevant to women's screening decision) presented in 11 subsets of 5 objects each. Of 25 objects initially identified, we selected 11 for the BWS instrument: provider-related factors: attitude, familiarity, and gender; setting-related: acceptance and cost; procedure-related: explanation during visit and timing/convenience of visit; personal fears/barriers: concerns about hygiene, addiction, and delivery/fear of results; and a general factor of feeling overwhelmed. CONCLUSIONS: Good practices for the development of stated preference surveys include considered assessment of the experimental design used and the preference factors included, and pretesting of presentation format. We demonstrate the development of a best-worst scaling study of homeless women's cervical cancer screening intervention preferences. Subsequent research will identify screening priorities to inform intervention design.